2018
DOI: 10.1177/0305829818773088
|View full text |Cite
|
Sign up to set email alerts
|

Race, the World and Time: Haiti, Liberia and Ethiopia (1914–1945)

Abstract: This article explores the role played by time in the maintenance of global racial difference with reference to the precarious sovereignties of Haiti, Liberia and Ethiopia during the interwar period. It suggests that the experiences of these states, understood through the discourses which sought to both support and undermine them, point to a shift away from juridical division in global order and towards a hierarchy framed in terms of racialised temporalities. While postcolonial scholarship can help us to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In the colonial present, national belonging is so all‐encompassing that it is not just states that are assigned statuses of “colonial temporalities” (“‘not‐yet’, stasis, regression, vanishing, or contemporaneous parody and failure” (Younis, :370)) but the bodies deemed to belong to those states. At the UK border, Somalis are imbued with the characteristics of their nation‐state as determined by the national order of things: they have failed in their accounts of themselves before they have even begun.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the colonial present, national belonging is so all‐encompassing that it is not just states that are assigned statuses of “colonial temporalities” (“‘not‐yet’, stasis, regression, vanishing, or contemporaneous parody and failure” (Younis, :370)) but the bodies deemed to belong to those states. At the UK border, Somalis are imbued with the characteristics of their nation‐state as determined by the national order of things: they have failed in their accounts of themselves before they have even begun.…”
Section: Resultsmentioning
confidence: 99%
“…For Western politicians and academics, Somalia has come to epitomize the ‘failed state’, a discourse which locates the ‘problem’ of failure as local, thereby sidestepping colonial guilt and eliminating Cold War and neo‐liberal policies. Younis (:370) argues that such epithets are continuations of the temporal and spatial logic of colonial‐racial difference:
‘the globalisation of international society’ [proceeds] on a two‐track temporality, on the one hand opening the door to a global synchrony of functionally undifferentiated political forms, but on the other adopting a stratification in political time which assigned various states (and their populations), by virtue of their ‘racial’ makeup, statuses of ‘not‐yet’, stasis, regression, vanishing, or contemporaneous parody and failure – extensions of colonial temporalities, but transposed onto a new political order.
Or as Gruffydd Jones (:182) notes more prosaically “the ‘failed state’ discourse obfuscates the historical social relations of crisis while legitimizing the reproduction of imperial social relations.” She further observes how the binaries of this discourse – success/failure, strong/weak, secure/fragile – echo that of the nineteenth century which legitimized colonialism on the basis of a civilized/uncivilized dichotomy. It must also be observed that these are gendered binaries (Massey, ; McClintock, ; Peterson, ).…”
Section: An Unthought Cosmology: the National Order Of Thingsmentioning
confidence: 99%
“…Secondly, as we have seen, sovereignty was a key goal in anticolonial projects seeking independence from imperial domination and remains a central demand in liberation movements today (Moreton-Robinson, 2015; Reynolds, 1996; Salt, 2018; Younis, 2018). Future investigations might question to what extent the notion of ‘colonial crisis’ and ‘responses to it’ can be subverted and rerouted by the colonised in acts of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…This article therefore contributes to interdisciplinary conversations on the question of race and racism. Although discussions of race and racism are present in IR (see among others Anievas et al, 2014; Henderson, 2013; Jones, 2008; Krishna, 2001; Sabaratnam, 2019; Shilliam, 2017; Thompson, 2013; Vitalis, 2015; Younis, 2018), they have at times overlooked their contestation as categories of analysis outside of the confines of the discipline. This ‘united front’ has undoubtedly been useful in carving out a space of possibility – where discussions around race and racism can take place in IR – but they also have the effect of glossing over some otherwise profound theoretical and political differences.…”
mentioning
confidence: 99%
“…Moreover, it is a process that is deeply interconnected with empire (Anghie, 2009; Keene, 2002; Reus-Smit, 2013) and, in the more recent past, with other, more or less violent, forms of control and domination. Critical, post-colonial and feminist scholars have shown that these include economic and financial standards (Chimni, 2006; Mozaffari, 2002), hierarchies generated by international law (Aalberts, 2014, Anghie, 2009; Pahuja, 2011), relations of gender dominance (Towns, 2009; Yuval-Davis, 1997), racial hierarchies (Sabaratnam, 2017; Yunis, 2018), stratifications of class (Agathangelou and Ling, 2009; Pal, 2018) and nationality (Chatterjee, 1993, 2010). A number of scholars have further stressed that, historically, resistance has been as central a pattern as domination in the making of the international system (Crawford, 2002; Lake and Reynolds, 2008; Meger, 2017).…”
Section: The Disjuncture Between the Expansion Of International Sociementioning
confidence: 99%